Habitat-adapted heterologous symbiont Salinispora arenicola promotes growth and alleviates salt stress in tomato crop plants - Becerril-Espinosa, Amayaly; Hernández-Herrera, Rosalba M.; Meza-Canales, Ivan D.; Perez-Ramirez, Rodrigo; Rodríguez-Zaragoza, Fabián A.; Méndez-Morán, Lucila; Sánchez-Hernández, Carla V.; Palmeros-Suárez, Paola A.; Palacios, Oskar A.; Choix, Francisco J.; Juárez-Carrillo, Eduardo; Lara-González, Martha A.; et al. (Frontiers in Plant Science, 2022)
In order to ensure food security under the current scenario of climate change and the accompanying ecological repercussions, it is important to search for new technologies and tools for agricultural production. Microorganism-based biostimulants are recognized as sustainable alternatives to traditional agrochemicals to enhance agricultural protection and production. Marine Actinobacteria are a well-known source of novel compounds for biotechnological uses. In addition, former studies have suggested that coral symbiont actinobacteria may aid in co-symbiotic photosynthetic growth and tolerance, increasing the probabilities of corals to survive abiotic stress. We have previously shown that this activity may also hold in terrestrial plants, at least for the actinobacteria Salinispora arenicola during induced heterologous symbiosis with a wild Solanaceae plant Nicotiana attenuata. Here, we further explore the growth promoting and stress relieving activity of S. arenicola in tomato plants and dig into the possible associated mechanisms. Tomato plants were grown under normal and saline conditions, and germination, bacteria-root system interactions, plant growth, photosynthetic performance, and the expression of salt stress response genes were analyzed. We found an endophytic interaction between S. arenicola and Tomato plants, which promotes germination and shoot and root growth, either under saline or non-saline conditions. Accordingly, photosynthetic and respective photoprotective performance was enhanced in line with the induced increase in photosynthetic pigments. This was further supported by the over expression of the thermal energy dissipation and electron distribution pathways, which fine-tune energy use efficiency and may prevent the formation of reactive oxygen species in the chloroplast. Furthermore, gene expression analyses suggested that a selective transport channel gene, SlHKT1,2, induced by S. arenicola may assist in relieving salt stress in tomato plants. The fine regulation of photosynthetic and photoprotective responses as well as the inhibition of the formation of ROS molecules seems to be related to the induced down regulation of other salt stress response genes, such as SlDR1A-related genes or SlAOX1b. Overall, our results demonstrate that the marine microbial symbiont S. arenicola establishes heterologous symbiosis in crop plants, promotes growth, and confers saline stress tolerance.